Teacher Creativity in the Use of Educational Games in Distance Mathematics Learning for Junior High School Students - Simamora, Rianita; Purba, Yoel Octobe; Simamora, Aprido (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Yogyakarta, 2024)
Playing is basically a natural activity that children mostly like. It can be used as a means of learning, at least learning about rules and roles. The aim of this research is to study how teacher's creativity influences the use of educational games in distance mathematics learning for eight graders. A number of thirty-five students from a public junior high school in North Sumatra involved in the study by completing a questionnaire regarding their perception on their teacher's creativity and reporting student's learning outcomes on mathematics subject. The authors did not conduct a test of learning outcomes but gathering the data from the school exam. The analysis shows there was contribution of teacher's creativity level into learning outcomes. Y = 50.030 + 0.424X with level of determination as much as 0.277. It can be concluded that it is evident that teacher creativity is an important factor. Although this study fails to show new conclusions, the large amount of determination level could trigger more elaborated research.